2018
DOI: 10.15666/aeer/1602_17971817
|View full text |Cite
|
Sign up to set email alerts
|

Tasos1 and Tatm20 Genes Expression and Nutrient Uptake in Wheat Seedlings May Be Altered via Excess Cadmium Exposure and Inoculation With Azospirillum Brasilense Sp7 Under Saline Condition

Abstract: TaSOS1 and TaTM20 gene expression and nutrient uptake in wheat seedlings may be altered via cadmium and inoculation with Azospirillum brasilense Sp7 under saline condition -1797 -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…A bacterial strain, SaMR12, up-regulates the expression of large number of metal transporter gene in S. alfredii plant [286]. As per Ghassemi and Mostajeran [287], Azospirillum brasilense enhances the Cd tolerance in T. aestivum with the help of Tatm20 gene. Jebara et al [288] reported PCS and F-box as the main genes for Cd tolerance in Sulla coronaria.…”
Section: Molecular Mechanisms Of Pgprmentioning
confidence: 92%
“…A bacterial strain, SaMR12, up-regulates the expression of large number of metal transporter gene in S. alfredii plant [286]. As per Ghassemi and Mostajeran [287], Azospirillum brasilense enhances the Cd tolerance in T. aestivum with the help of Tatm20 gene. Jebara et al [288] reported PCS and F-box as the main genes for Cd tolerance in Sulla coronaria.…”
Section: Molecular Mechanisms Of Pgprmentioning
confidence: 92%
“…Exogenous applications of PGPR a strain, Streptomyces strain IT25, decreased catalase (CAT),and it is reported that PGPRs upregulated SOD (superoxide dismutase), POD (peroxidase), and PPO (plant polyphenol oxidases) genes to sequester Cd stress ( Khanna et al, 2019 ; Abbasi et al, 2020 ) ( Table 6 ). Azospirillum brasilense may ameliorate the negative effects of Cd stress by upregulation of lower Na/K ratio, TaSOS1 transcript level, proline, higher pigments, and antioxidant activities to improve dry weight ( Ghassemi and Mostajeran, 2018 ). PGPR-mediated remediation of HMs and promotion of plant growth depend on PGPR strains coded by several genes and must be understood to build a multidimensional PGPR strain to perform multidimensional functions.…”
Section: Remediation Of Cadmium-polluted Soilsmentioning
confidence: 99%
“…In the case of cadmium, Ta t m20 gene codifies a transmembrane transport that is expressed in the presence of Cd in wheat. When wheat plants were inoculated with Azospirillum brasilense, this gene was expressed much less than in the absence of the inoculation suggesting that A. brasilense helps plants to decrease Cd uptake and accumulation [97]. In this study, we also studied the expression of TasSOS1 gene involving in keeping the plant cell homeostasis in the presence of high salt concentrations.…”
Section: Molecular Mechanisms In the Bacteria-plant Interactions Undementioning
confidence: 99%
“…In contrast to Ta t m20 gene, TasSOS1 is overexpressed in inoculated plants under salinity stress. This overexpression maintains the homeostasis in plants and makes plant more tolerant to salt excess [97]. In M. sativa plants grown under heavy metal conditions, the genes involved in the phytochelatins synthesis were overexpressed in inoculated plants helping plant to detoxify and to grow in the presence of this stress.…”
Section: Molecular Mechanisms In the Bacteria-plant Interactions Undementioning
confidence: 99%